Antithrombotic therapy and major adverse limb events in patients with chronic lower extremity arterial disease: systematic review and meta-analysis from the European Society of Cardiology Working Group on Cardiovascular Pharmacotherapy in Collaboration with the European Society of Cardiology Working Group on Aorta and Peripheral Vascular Diseases. Issue 2 (8th August 2019) - Savarese, Gianluigi; Reiner, Martin F; Uijl, Alicia; D'Amario, Domenico; Agewall, Stefan; Atar, Dan; Baumgartner, Iris; Borghi, Claudio; De Carlo, Marco; Drexel, Heinz; Kaski, Juan Carlos; Kjeldsen, Keld P; et al.
Abstract: Aims: The role and selection of antithrombotic therapy to improve limb outcomes in chronic lower extremity artery disease (LEAD) is still debated. We conducted a meta-analysis to examine the efficacy and safety of antithrombotic and more intense antithrombotic therapy on limb outcomes and limb salvage in patients with chronic LEAD. Methods and results: Study inclusion criteria were: enrolment of patients with LEAD, randomized allocation to more vs. less intense antithrombotic therapy [more vs. less intense single-antiplatelet therapy (SAPT); dual-antiplatelet therapy vs. SAPT; dual antithrombotic therapy vs. SAPT or oral anticoagulant]; enrolment of ≥200 patients; reporting of at least one of following outcomes: limb amputation or revascularization. Seven randomized studies enrolling 30 447 patients were included. Over a median follow-up of 24 months, more vs. less intense antithrombotic therapy or placebo significantly reduced the risk of limb revascularization [relative risk (RR) 0.89, 95% confidence interval (CI) 0.83–0.94] and limb amputation (RR 0.63, 95% CI 0.46–0.86), as well as stroke (RR 0.82, 95% CI 0.70–0.97). There was no statistically significant effect on the risk of myocardial infarction (RR 0.98, 95% CI 0.87–1.11), all-cause (RR 0.93, 95% CI 0.86–1.01), and cardiovascular death (RR 0.97, 95% CI 0.86–1.08). Risk of major bleeding increased (RR 1.23, 95% CI 1.04–1.44). Conclusion: In patients with LEAD, more intense antithrombotic therapy reduces the risk of limb amputation and revascularization as well as stroke with an increase in the risk of bleeding events.